Sosialisasi Sadar Keselamatan Berlalu Lintas Pada Siswa SMA Negeri 8 Jakarta - Sonya Sidjabat; Sri Handayani; Abdullah Ade Suryobuwono (Institut Transportasi dan Logistik Trisakti, 2022)
Safety is one of the attributes of transportation in general and road transportation or traffic and road transportation in particular. Safety is something that is priceless, but few people are aware of maintaining their own safety. Road traffic safety is a condition where everyone avoids the risk of accidents during traffic caused by human, vehicles, roads and environment (RI Law No 2, 2009). Many high school students violate traffic rules and lack understanding of traffic norms. Such as breaking traffic lights or running lights, driving a motorbike/car without a driver’s license, pillion not using a helmet, not turning on the lights during the day, not using a seat belt while driving. Because the understanding of the traffic norms in high school students has a big impact, according to the conditions that are increasing day by day, for this reason we propose participation in the form community service program in the form safety road socialization to students in grade 11 and 12 at SMAN 8 Jakarta. The socialization was carried out by explaining the importance of understanding traffic norms and obeying traffic regulations. Through this community service program, it is hoped that it can arouse the awareness of the hearts of students to increasingly obey traffic rules and understand more about traffic norms.